Consultório na Rua em Maceió/AL: o olhar de pessoas em situação de rua - Ferreira, Cíntia Priscila da Silva (2015)
The Office strategy Street is recent, it emerged from the convergence of different pop-ulation to the attention of experiences on the streets. The aim of this es-all is to analyze the strategy's Office in the street in Maceió / AL, in view of its users, with the specific objectives: 1) to identify, from the accounts of users, the actions taken by Offices in the street; 2) to analyze the challenges and possibilities of the Office in Street; 3) analyze the meanings that the Office at Rua has for users. This research adopted the qualita-tive approach. The scenario chosen were the Office of the playing fields in the street of the city of Maceió, Alagoas. The municipality has six teams in Street Offices. The research subjects were people on the streets served by the Office strategy Street. In-clusion criteria were: being over 18, being on the streets and have already been an-swered by the Office in Street. For data collection was carried out the technique of semi-structured interview being conducted 18 interviews, from September 2014 to February 2015 following the theoretical saturation of data. For data analysis we used the categorical content analysis technique by theme. The results showed three cate-gories. The first, "the meaning of life on the streets," portrays a context of needs, short-comings and abuses. The second, "the Office in the street as he is," reveals the chal-lenges and potential of this strategy. And the third, "What's Office in Street is?" Reveals social support, affection and change of perspective for those in the streets. The study results showed that the Office strategy Street is assessed positively by users, which point they receive social support, affection, and in some cases chance to change their lives. In addition, they highlighted the access to health services, team commitment and the established relationship of respect between staff and users. However, the chal-lenges are also indicated, including the inadequacy of organizational structure, preju-dice and stigma of some professionals of the Health Care Network services compared to people in the streets. This study points to the need for engagement of management and health professionals who are in different spaces of the pessos care network living on the streets. Also points to the need to address stigma and prejudice in relation to this population. We recommend a political action with the people on the streets to rec-ognize their status as subjects and citizens face the challenges and take the fight for their dignity and their rights.